Connecting Emotions and Learning: A Collaborative Approach Based on Emotional Intelligence - Zuñiga Abregu, Romi Rubi; Suxe Ramírez, María Alicia; Yepez Pretel, Nidia Erlinda (LACCEI, 2025)
The present research aimed to understand the relationship between emotional intelligence and collaborative learning in university students. The findings demonstrate that higher levels of emotional competencies such as emotional regulation, empathy, and interpersonal skills allow young people to learn collaboratively, which better channels learning in groups, improving academic performance and emotional well-being. However, the study also shows that the strength of this relationship varies depending on the educational context and teaching methodologies. In conclusion, fostering emotional intelligence in children and adolescents in collaborative environments is a key factor in enhancing learning processes in higher education